The Effect Of Liquidity, Profitability, Price Earning Ratio and Interest Rates On Company Stock Returns: Sub Sector of Property and Real Estate Listed on the IDX for the Period 2018 – 2023 - Neni Nurisnaini; Riska Dwi Wulandari; Yoyon Supriadi (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study analyzes the effect of liquidity, profitability, Price Earnings Ratio (PER), and interest rates on stock returns in property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2018–2023. The research is motivated by fluctuations in stock performance within the sector, which are strongly associated with macroeconomic uncertainty and company fundamentals. Using a quantitative approach, six companies were selected through purposive sampling based on specific criteria, and panel data consisting of 36 observations (6 companies × 6 years) was analyzed using multiple linear regression with SPSS version 22. The empirical results indicate that liquidity (CR) and profitability (ROE) have a positive and statistically significant effect on stock returns, while PER shows no significant influence. Conversely, interest rates have a negative and significant impact on stock returns. Simultaneously, all independent variables significantly influence stock returns, as reflected in the regression model (R² = 43.1%). These findings suggest that investors should consider the stability of company financial performance and macroeconomic rate movements when making investment decisions. This study contributes theoretically by reinforcing the signaling and market efficiency theories in the context of the Indonesian capital market, and provides practical implications for issuers to optimize financial indicators to enhance investor confidence and stock value. Further research is recommended to incorporate moderating variables such as economic crisis or ESG disclosure, as well as extending the study period to capture post-pandemic recovery dynamics.   Keywords: Capital Market, Interest Rates, Liquidity, Profitability, Stock Returns